On the Cesàro operator in the Hardy space in the upper half plane - Andreev, Valentin V.; Bekker, Miron B.; Cima, Joseph A. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9 We consider the Cesàro operator in the Hardy space in the upper half plane. We provide a new simple proof of boundedness of this operator and show that this operator is equal to the sum of the identity operator and a unitary operator, which implies its normality.